Analysis of the Relationship of Mix Marketing with Patient Loyalty and Satisfaction in Hospital - Syamsul Huda; Anik Yuliati (Eduvest - Journal of Universal Studies, 2022)
This study aims to analyze the relationship between the marketing mix and patient loyalty and satisfaction at the hospital. The research method used in this research is descriptive qualitative method. The type of data used in this study is qualitative data, which is categorized into two types, namely primary data and secondary data. Sources of data obtained through library research techniques (library studies) which refers to sources available both online and offline such as: scientific journals, books and news sourced from trusted sources. These sources are collected based on discussion and linked from one information to another. Data collection techniques used in this study were observation, interviews and documentation. This data was analyzed and then drawn conclusions. Based on the description analysis, it can be concluded that there is a relationship between the marketing mix on loyalty and patient satisfaction. After the analysis, it can be seen that all elements in the marketing mix have an influence on patient loyalty to reuse services at the hospital. After the analysis, it can be seen that the relationship between the marketing mix and customer satisfaction is very influential because the marketing mix is ​​a factor or market element used to satisfy customers.